Determinants of information users in local public accounting - Syed Raziuddin Ahmad; Raj Bahadur Sharma; Ijaz Ali; Asif Baig; Imran Ahmad Khan (Cogent Business & Management, 2022)
The purpose of this paper was to identify the information users assumed by the financiers of local governments in India and to empirically clarify the determinants of these users. The Ministry of Finance requires local governments in India to prepare public accounting information based on uniform standards from the fiscal year 2017 and is currently examining how and by whom the prepared accounting information can be utilized. In the U.S., where accrual accounting has already been adopted by states and local governments, the Governmental Accounting Standards Board (GASB) has conducted a survey of financiers and stakeholders to determine the needs of information users for financial reports in the development of accounting standards. Therefore, this paper predicts that when a local government has a large amount of debt (debt hypothesis), when there is a large demand for public goods from citizens (public goods hypothesis), and when the chief executive has experience in using financial statements (upper management hypothesis), local government treasurers will actively consider information disclosure measures in anticipation of outsiders using the information. The results of the questionnaire survey of 1,788 local government financiers indicated that the main information users of public accounting information assumed by local government financiers are government officials. As a result of the factor analysis, we found that information users can be roughly classified into government officials and other information users. We also found that in local governments where financiers assume that information users use accounting information, the chief executive has experience as a corporate officer.
Keywords: M40; H72; H83; M41; 650; Accrual Accounting; Debt Ratios; Financiers; Information Users; Public Accounting